Elevated alcohol and sexual risk behaviors among young Thai lesbian/bisexual women - Shivani A. Patel (2018)
Background: Little empirical data have been published about drinking or sexual behaviors among Thai lesbians. We examine the association of sexual identity with established indicators of alcohol- and sexual-related health behaviors among female bar patrons. Methods: We conducted a cross-sectional study among women (N= 121) aged 18-24 who frequented popular drinking establishments in Chiang Mai, Thailand. We used general linear modeling techniques to estimate associations between sexual identity and positive alcohol expectancy, harmful drinking, age at sexual debut, and number of lifetime sexual partners. Results: Nearly one-third of women aged 18-24 recruited from Chiang Mai drinking venues identified as lesbian/bisexual. As compared to their heterosexual counterparts, lesbian/bisexuals reported higher positive alcohol expectancy scores, more harmful drinking, earlier age at sexual debut, and higher number of lifetime sexual partners. In adjusted models, lesbian/bisexual identity was associated with higher positive alcohol expectancy (β= 1.94 points; 95% CI: 0.75, 3.13), earlier age at sexual debut (β= -0.85 years; 95% CI: -1.46, -0.23), and higher number of lifetime sexual partners (rate ratio = 1.70; 95% CI: 1.22, 2.37). Conclusion: Lesbian/bisexual women in this study engaged in multiple behaviors that are potentially harmful to health, which may in turn place this group at heightened risk for alcohol abuse and sexually transmitted infections in Thailand. The clustering of alcohol- and sexual-related risk behaviors, and its consequences for health outcomes in this population, should be explored in future research and may be an important point of intervention. © 2012 Elsevier Ireland Ltd.